The History of Turkey : Grandeur and Grievance - Reinkowski, Maurus (Ottoman and Turkish Studies, 2023)
A comprehensive, readable history of the Republic of Turkey that gives equal weight to all periods in the first century of the Republic of Turkey.The republican order of Turkey seems not to have changed much since its foundation in 1923, but there were dramatic transformations: From Atatürk's modernization dictatorship in the 1920s and 1930s, over the massive migration into the cities and the military coups in the second half of the twentieth century, up to Recep Tayyip Erdoğans electoral autocracy since the 2010s. This book makes us understand Turkey's historical trajectory in the nineteenth and twentieth centuries and the fate of its various communities and ethnic groups-in particular Alevis and Kurds-and argues that a particular trait of Turkish political culture is its constant fluctuation between confidence and contention, grandeur and grievance.